Digital Sermons and Youth Engagement: Measuring the Effectiveness of Islamic Preaching on TikTok - Derma Seprianti; Tri Handoyo; Desi Firmasari; Eti Efrina; N. Baskautshar (Tinta Emas Institute, 2024)
This study quantitatively examines the effectiveness of Islamic preaching (dakwah) content on TikTok in fostering youth engagement and religious behavioral intentions. Grounded in the Heuristic-Systematic Model and Source Credibility Theory, the research investigates how message quality, preacher credibility, and content interactivity influence behavioral engagement and subsequent religious intentions. Data from 450 young Indonesian TikTok users were analyzed using Structural Equation Modeling (SEM). The results identify preacher credibility as the strongest predictor of behavioral engagement (β = 0.41, p < 0.001), followed by message quality (β = 0.32, p < 0.001) and content interactivity (β = 0.28, p < 0.001). Behavioral engagement significantly influences religious intentions (β = 0.53, p < 0.001) and acts as a significant partial mediator, translating the effects of independent variables into religious behavioral intentions. These findings underscore the pivotal role of source credibility and active audience participation in digital religious persuasion, offering practical insights for religious communicators to design effective digital preaching strategies on short-form video platforms. The study contributes to digital religion literature by validating the complementary nature of heuristic and systematic processing in religious content evaluation on social media.